Pengaruh Financial Target dan Financial Stability terhadap Financial Statement Fraud - Robert Jao; Ana Mardiana; Anthony Holly; Exel Chandra (YUME : Journal of Management, 2021)
The purpose of this study was to investigate the effect of financial target and financial stability on financial statement fraud. The study population consisted of companies on the Indonesia Stock Exchange (IDX) from 2017-2019.The sampling technique used was purposive sampling. The method used in this research is quantitative research methods. The data source consists of secondary data obtained from the Indonesia Stock Exchange (IDX). This type of documentary data consists of company financial statements from 2017-2019. The result showed that financial target and financial stability had a significant effect on financial statement fraud, indicating that companies that have pressure can enhance fraud behavior.Keywords:Financial target, financial stability, financial statement fraud